ADMISSIBILITY OF CONFESSION UNDER INDIAN EVIDENCE ACT, 1872 - Malik, Neeraj (ShodhKosh: Journal of Visual and Performing Arts, 2023)
In Indian criminal law, confessions are defined by the 1872 Indian Evidence Act. Confessions of guilt have legal implications. The Act classifies admissions as judgemental, out-of-court, and retracted. Judgemental confessions are admissible, whereas extrajudicial confessions are examined for pressure. Retracted confessions are carefully reviewed and may need third-party verification. Coerced, forced, or promised confessions and law enforcement confessions are illegal. Voluntary confessions protect the accused’s identity. Mind, confession, and accused rights awareness determine voluntariness in court. Legal balance between law enforcement and private liberty ensures confession voluntariness in India. Other states prohibit forced confessions less strongly than the Indian Evidence Act. Unique to India, the Act forbids police confessions. Torture is defined, investigated, compensated, and punished under the 2017 Prevention of Torture Bill. It must be narrowed to balance law enforcement and freedoms enjoyed by individuals. Law enforcement and personal liberty deal effectively with detainee admissions. The Indian police and judge approach confessions differently to avoid prisoner torture and coercion. Section 25 of the Indian Evidence Act forbids police admissions for wrongdoing and power imbalance. According to Section 164 of the Code of Criminal Procedure, magistrate confessions are voluntary and honest. Courts consider the confession’s conditions, medical records, and the accused’s education, social status, and mental health. Criminal confession retraction affects trial evidence and poses admissibility and evidentiary value questions. Retracted confessions are less trustworthy than uncontested ones, thus courts must closely check them before convicting. If followed, procedural and technological flaws do not invalidate confessions, but Section 164 noncompliance does.